Inherited IFNAR1 Deficiency in a Child with Both Critical COVID-19 Pneumonia and Multisystem Inflammatory Syndrome - Hassan Abolhassani (2287858) (2022)
Background Inborn errors of immunity (IEI) and autoantibodies to type I interferons (IFNs) underlie critical COVID-19 pneumonia in at least 15% of the patients, while the causes of multisystem inflammatory syndrome in children (MIS-C) remain elusive. Objectives To detect causal genetic variants in very rare cases with concomitant critical COVID-19 pneumonia and MIS-C. Methods Whole exome sequencing was performed, and the impact of candidate gene variants was investigated. Plasma levels of cytokines, specific antibodies against the virus, and autoantibodies against type I IFNs were also measured. Results We report a 3-year-old child who died on day 56 of SARS-CoV-2 infection with an unusual clinical presentation, combining both critical COVID-19 pneumonia and MIS-C. We identified a large, homozygous loss-of-function deletion in IFNAR1, underlying autosomal recessive IFNAR1 deficiency. Conclusions Our findings confirm that impaired type I IFN immunity can underlie critical COVID-19 pneumonia, while suggesting that it can also unexpectedly underlie concomitant MIS-C. Our report further raises the possibility that inherited or acquired dysregulation of type I IFN immunity might contribute to MIS-C in other patients. Other Information Published in: Journal of Clinical Immunology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10875-022-01215-7